2013
DOI: 10.1371/journal.pone.0057825
|View full text |Cite
|
Sign up to set email alerts
|

Medical Attendance for Lower Urinary Tract Symptoms Is Associated with Subsequent Increased Risk of Outpatient Visits and Hospitalizations Based on a Nationwide Population-Based Database

Abstract: IntroductionLower urinary tract symptoms (LUTS), which encompass storage, voiding, and postmicturition symptoms, are highly prevalent and recognized globally. Based on a nationwide population-based database, this study tests the hypothesis that medical attendance for LUTS is associated with a subsequent increase in the number of outpatient visits and hospitalizations, with differences among medical specialties and age groups.MethodsParticipants were selected from a random population sample of approximately one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In accordance with our study series on LUTS [1], [11], we scrutinized all the relevant ICD-9-CM codes and defined the following categories of codes for service claims as LUTS: (A) storage symptoms, including hypertonicity of bladder (ICD-9-CM code 596.51), frequency and polyuria (788.4), stress urinary incontinence in women (625.6) and men (788.32), urgent incontinence (788.31), nocturnal enuresis (788.36), nocturia (788.43), mixed incontinence (788.33); (B) voiding symptoms, including retention of urine (788.2), splitting & slowing of urine stream (788.6), and post-void dribbling (788.35); and (C) benign prostate hyperplasia (BPH) in men (600). Because LUTS are inseparable from clinical BPH [12], men with a BPH code, regardless of corresponding codes for storage/voiding symptoms or not, were all categorized as LUTS.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with our study series on LUTS [1], [11], we scrutinized all the relevant ICD-9-CM codes and defined the following categories of codes for service claims as LUTS: (A) storage symptoms, including hypertonicity of bladder (ICD-9-CM code 596.51), frequency and polyuria (788.4), stress urinary incontinence in women (625.6) and men (788.32), urgent incontinence (788.31), nocturnal enuresis (788.36), nocturia (788.43), mixed incontinence (788.33); (B) voiding symptoms, including retention of urine (788.2), splitting & slowing of urine stream (788.6), and post-void dribbling (788.35); and (C) benign prostate hyperplasia (BPH) in men (600). Because LUTS are inseparable from clinical BPH [12], men with a BPH code, regardless of corresponding codes for storage/voiding symptoms or not, were all categorized as LUTS.…”
Section: Methodssupporting
confidence: 89%
“…By 2009 more than 99% of the total population in Taiwan has been covered by the compulsory and universal NHI since its implementation in March 1995. The details of NHIRD were described in our previous studies [1], [11]. In brief, from the registration files and NHI claims data between 2000 and 2009, a random sample of one million enrollees (approximately 5% of Taiwan's population) has been established as a representative cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings are consistent with results of a study by Wu et al . which reported that patients with BPH/lower urinary tract symptoms (LUTSs) had higher rates of outpatient visits and hospitalization than a comparison group 6. In addition, another similar study reported that patients with LUTSs were associated with increased resource use in terms of emergency room visits, medical provider visits, and hospitalizations than were those without LUTSs 7…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al . reported that a poor quality of life among people with BPH/LUTSs can lower the threshold of outpatient visits and hospitalization requests 6. Those potential medical conditions may increase the opportunity to use urological and nonurological health services among patients with BPH.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences exist in the age, gender, or insured amount distributions between patients in our data and the original NHIRD with p value = 0.187 [ 10 ]. The NHIRD has been used by many researchers [ 11 ] for dozens of published studies. The Institutional Review Board (IRB) of Chi Mei Foundation Hospital approved this study and waived the requirement of informed consent because the datasets in the NHIRD have no identifiable personal information.…”
Section: Methodsmentioning
confidence: 99%